2019
DOI: 10.1109/tcbb.2018.2858808
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on Predicting Functional Role of Metagenomes Using Machine Learning Methods

Abstract: "Metagenomics" is the study of genomic sequences obtained directly from environmental microbial communities with the aim to linking their structures with functional roles. The field has been aided in the unprecedented advancement through high-throughput omics data sequencing. The outcome of sequencing are biologically rich data sets. Metagenomic data consisting of microbial spe-cies which outnumber microbial samples, lead to the "curse of dimensionality". Hence the focus in metagenomics studies has moved towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(78 reference statements)
0
10
0
1
Order By: Relevance
“…The model outputs the predictive class majority voting amongst the constituent individual trees [21]. Several studies have applied RF for the prediction of metagenomic functions [7][8][9]. b. Reg-LR.…”
Section: Description Of ML Methods Used In the Workflowmentioning
confidence: 99%
See 3 more Smart Citations
“…The model outputs the predictive class majority voting amongst the constituent individual trees [21]. Several studies have applied RF for the prediction of metagenomic functions [7][8][9]. b. Reg-LR.…”
Section: Description Of ML Methods Used In the Workflowmentioning
confidence: 99%
“…We found that the incorporation of the phylogenetic tree structure into analysis has potential to increase the prediction power. More accurate predictions were obtained with the phylogeny-aware pipeline as proposed in [11], when benchmarked with other nonphylogenetic [7][8][9] and phylogenetic-based approaches [12][13][14]. Some high-level visualizations and their applicability to our data are also presented.…”
Section: Introduction (Heading 1)mentioning
confidence: 94%
See 2 more Smart Citations
“…Các thí nghiệm đã được tiến hành để dự đoán bệnh dựa trên dữ liệu Metagenomic, sử dụng nền tảng trong R-project ở trang web http://www.R-project.org, phiên bản 3.0.4. (Wassan, 2018). Các gói khác nhau liên quan đến các mô hình máy học-Machine Learning (ML) và bộ thông số cấu hình tối ưu có liên quan được sử dụng trong nghiên cứu này được liệt kê dưới đây (Bảng 2).…”
Section: Cài đặT Thực Nghiệmunclassified